Restrukturisasi Organisasi Perangkat Daerah Berdasarkan Peraturan Pemerintah Nomor 41 Tahun 2007 (Studi Tentang Penataan Organisasi Perangkat Daerah di Kabupaten Murung Raya) - Faozan, Haris; Zulpikar, Zulpikar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
This study was aimed at anlizing the arrangement of the Regional Organizational Apparaturs of Murung Raya Regency based on Government Regulation No. 41 Year 2007 concerning Regional Organizational Apparatus. The study analysed the exsisting condition, local needs, and related rules of laws, and vision and mission of the regional government of Murung Raya Regency.